2016
DOI: 10.1128/genomea.00843-16
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Sequence of a Ranavirus Isolated from Short-Finned Eel ( Anguilla australis )

Abstract: The short-finned eel ranavirus (SERV) was isolated from short-finned eel imported to Italy from New Zealand. Phylogenomic analyses revealed that SERV is a unique member of the genus Ranavirus, family Iridoviridae, branching at the base of the tree near other fish ranaviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Large product PCR assays have been used in phylogenetic studies of reptilian ranaviruses (Stöhr et al, 2015). As the cost of sequencing decreases, it is becoming increasingly popular to use high throughput sequencing methods to more accurately identify and characterise viral isolates (Hick et al, 2016; Subramaniam et al, 2016).…”
Section: Diagnostics and Surveillancementioning
confidence: 99%
“…Large product PCR assays have been used in phylogenetic studies of reptilian ranaviruses (Stöhr et al, 2015). As the cost of sequencing decreases, it is becoming increasingly popular to use high throughput sequencing methods to more accurately identify and characterise viral isolates (Hick et al, 2016; Subramaniam et al, 2016).…”
Section: Diagnostics and Surveillancementioning
confidence: 99%
“…The two isolates PEV_DK1 and REV 282/I02 were amplified in epithelioma papulosum cyprini cells until the cytopathic effect was complete, and then the resulting supernatant was clarified and the total nucleic acid was purified from the clarified supernatant, as previously described ( 7 ). DNA libraries were prepared using the Nextera XT DNA kit (Illumina), and sequencing was performed using a v3 chemistry 600-cycle kit on an Illumina MiSeq platform.…”
Section: Genome Announcementmentioning
confidence: 99%
“…The Rmax and CoIV isolates were propagated in bluegill fry (BF-2) cells as previously described (4) and harvested at third and fourth passages, respectively. Cell culture supernatant was clarified at 3,000 × g for 20 min, and total nucleic acids were purified using a DNeasy blood and tissue kit (Qiagen).…”
Section: Genome Announcementmentioning
confidence: 99%
“…A total of 100 putative ORFs were predicted in Rmax and 98 in CoIV; compared to other closely related fish ranaviruses, 100 putative ORFs were predicted in EHNV and 111 in short-finned eel ranavirus (SERV, GenBank accession no. KX353311) (4). Comparative genomic analyses revealed that Rmax and CoIV are nearly identical to each other, except for a nonsense mutation leading to an early stop codon in CoIV (ORF70 in Rmax, unannotated ORF located between ORFs 66 and 67 in EHNV) and the absence of a gene in CoIV (ORF62 in Rmax, ORF58L in EHNV).…”
Section: Genome Announcementmentioning
confidence: 99%